Degradable magnesium implants: improving bioactive and antibacterial performance by designed hybrid coatings - Merlo, Julieta Letizia; Detsch, Rainer; Cere, Silvia; Boccaccini, Aldo R.; Ballarre, Josefina (Journal of Materials Research, 2021)
Magnesium and its alloys are promising material candidates for degradable fracture fixation devices due to their suitable mechanical properties and biocompatibility; however, their fast corrosion in aqueous media causes pain and swelling. In this study, a hybrid coating system composed by a sol–gel silica-based matrix with bioactive glass microparticles and silica–gentamicin nanoparticles was deposited by spray technology on magnesium AZ91D alloy. The coating was homogeneously distributed on the surface and protected the degradation of AZ91D alloy in simulated body fluid for at least 28 days, preventing the pH increase of the solution and accelerating the formation of calcium phosphate-related compounds on the surface. Moreover, inhibition of bacteria growth was proved for Staphylococcus aureus and Escherichia coli and increased cell adhesion and proliferation of ST-2 and differentiated MC3T3-E1 cells was shown. The generated coating is a promising surface treatment for providing bioactive and antibacterial proprieties to new degradable implants. Graphic abstract: [Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2021-03-05
Keywords: Coating; Mg alloy; Spray deposition

Functional behavior of chitosan/gelatin/silica-gentamicin coatings by electrophoretic deposition on surgical grade stainless steel - Aydemir, Tuba; Liverani, Liliana; Pastore, Juan I.; Ceré, Silvia M.; Goldmann, Wolfgang; Boccaccini, Aldo R.; Ballarre, Josefina (Materials Science and Engineering C, 2020)
Metals are used in several orthopedic applications as fixation elements for the stabilization of fractures or as prostheses. One of the most common orthopedic biomaterials in many developing countries is surgical grade stainless steel (SS). However, its use as permanent implant in orthopedic surgery is conditioned due to its limited corrosion resistance in physiological media, lack of osseointegration, and absence of antibacterial effect. The aim of this work is to generate a degradable coating with antibacterial properties for stainless steel to be used in implants/medical devices. The coating is composed of a biopolymer/silica-gentamicin nanoparticles composite obtained by electrophoretic deposition (EPD) on surgical grade stainless steel plates. The coating surface was characterized by microscopic examination, and in vitro performance was evaluated after immersion in phosphate-buffered saline (PBS) solution, simulated body fluid (SBF), and cell culture medium, to analyze coating degradation, antibiotics release, cell attachment (ST-2 stromal cells), and antibacterial (Escherichia coli and Staphylococcus aureus) properties. EPD coatings were uniform and covered homogeneously the surface of the SS substrate. Also the distribution of silica-gentamicin nanoparticles was homogeneous on the coated area. The degradation of the chitosan-gelatin coatings was evident after 7 days of immersion. The gentamicin release led to excellent antibacterial behavior at 24 h, meanwhile the cell proliferation (at 7 days culture) was not inhibited. The results show that the coating system exhibits promising behavior which could contribute to prevent hospital infections at early implantation times.
CRIS-Team Scopus Importer:2020-06-02
Keywords: Chitosan; Electrophoretic deposition; Gelatin; Prevention of infections; Silica-gentamicin nanoparticles; Stainless steel implants

Morphological and mechanical characterization of chitosan/gelatin/silica-gentamicin/bioactive glass coatings on orthopaedic metallic implant materials - Aydemir, Tuba; Pastore, Juan I.; Jimenez-Pique, Emilio; Roa, Joan Josep; Boccaccini, Aldo R.; Ballarre, Josefina (Thin Solid Films, 2021)
Metals are the most widely used materials for orthopedics and dentistry due to their high mechanical properties. However, for certain uses like fixation plates and screws, dental implants, and osseo-articular prosthesis, their surface characteristics such as non-toxic and non-corrosive behavior, good cell adhesion and proliferation, and resistance to bacterial biofilm formation should be accompanied with high mechanical performance. One way to improve metallic implant performance in vivo is to coat them with biopolymer or inorganic thin films. This work describes two multifunctional coating systems for orthopedic titanium and stainless steel implants. Titanium implants were coated with a system consisting of a base hybrid sol-gel layer with bioactive glass particles (applied via spraying) and a top chitosan/gelatin layer with silica-gentamicin nanoparticles (applied via electrophoretic deposition, EPD). Stainless steel implants, which are designed to be removable, were coated only with the top chitosan/gelatin/ silica-gentamicin nanoparticles layer with the aim of providing a temporal attachment to bone and to combat possible bacterial adhesion. The microstructural and mechanical characterization of the coatings was conducted by optical microscopy, transmission and scanning electron microscopy, digital image processing, as well as nanoindentation and nanoscratch tests to advance the understanding of their elastic-plastic, morphologic and adhesive behavior. The coatings were homogeneous, providing good coverage to both substrates. Their surface properties, such as roughness and wettability, indicate that they represent excellent substrates for cell attachment. Bioactive glass particles can be added to titanium implant systems as bioactive components without affecting adhesion or mechanical performance of the chitosan/gelatin/silica-gentamicin nanoparticle EPD coatings. The increase in both hardness and elastic modulus of the coated systems could be due to the presence of the silica-gentamicin nanoparticles and their compaction during the penetration of the indenter. When the samples are subjected to scratch tests, the critical load increases with the reinforcement of the coatings by the silica-gentamicin nanoparticles absorbing the applied load and maintaining the elastic properties of the coatings.
CRIS-Team Scopus Importer:2021-07-02
Keywords: Bioactive glasses; Biopolymers; Electrophoretic deposition; Functional coatings; Mechanical properties; Metallic implants

Versatile bioactive and antibacterial coating system based on silica, gentamicin, and chitosan: Improving early stage performance of titanium implants - Ballarre, Josefina; Aydemir, T.; Liverani, Liliana; Roether, Judith; Goldmann, Wolfgang; Boccaccini, Aldo R. (Surface & Coatings Technology, 2019)
The aim of this work is to develop and characterize a multifunctional and dual surface coating system for titanium orthopedic implants by applying two different cost-effective, scalable, and non-complex coating technologies (spray and electrophoretic deposition). The first deposit is formed by a sprayed hybrid sol-gel layer combined with bioactive glass particles (45S5, BG), and the outer part of the dual coating consists of a chitosan-gelatin/silica (Si) - antibiotic (gentamicin, Ge) composite layer applied by electrophoretic deposition. The application of sol-gel enclosed BG drops onto the surface was done to enhance the bioactivity of the double-layered surface coating system. After the BG is dissolved, thus generating a calcium‑silicon rich medium, the re-deposition of hydroxyl‑carbonate apatite occurs. Regarding the antibacterial inhibition properties, antibacterial activity to both strains used (S. aureus and E. coli) was obtained for the chitosan/gelatin/Si[sbnd]Ge nanoparticle coatings on titanium substrates, showing a large inhibition area around the samples. Both the bare Ti samples and the coatings with chitosan/gelatin matrix did not successfully inhibit bacterial growth. As expected, the presence of silica-based glasses and coatings based on amorphous silica enhanced cell viability. The deposition of BG was done with the aim of extending the bioactive effect of the system, considering the presence of a porous degradable organic layer deposited on top, which was shown to be partially degraded after 7 days. The sol gel sprayed BG layer combined with chitosan/gelatin biopolymers filled with Si[sbnd]Ge nanoparticles presents a suitable technology to generate bioactive and antibacterial surfaces to enhance Ti implant performance.
CRIS-Team Scopus Importer:2019-12-13
Keywords: Antibacterial effect; Bioactive glass; Bioactivity; Electrophoretic deposition; Silica-gentamicin nanoparticles; Titanium